The Irvingtonian Avifauna of Cumberland Bone Cave, Maryland - James, Helen F. (Zootaxa, 2020)
The early and mid-Pleistocene avian communities of North America are best known from the Rocky Mountain region and peninsular Florida. In the Appalachian Mountain region, only a small number of avian bones from mid-latitude cave deposits have been attributed to this time period. Here, I enlarge this record by reporting on bird bones from Cumberland Bone Cave in western Maryland, a well-known locality for large and small Irvingtonian mammals and other vertebrates. The taxa identified encompass ground birds, waterfowl, a hawk, two eagles, a vulture, an owl, a jay, a flycatcher, a junco or sparrow, and a finch. No purely boreal elements are confirmed as part of the avian assemblage, and all of the extant species that are positively or tentatively identified in the assemblage still occur in the region today. An immature bone referred to the Black Vulture (Coragyps atratus (Bechstein)) represents an Irvingtonian breeding record for the species in Maryland. This record occurs at the northern limit of the current breeding range for the genus. Extinct species in the assemblage include the Passenger Pigeon (Ectopistes migratorius (Linnaeus)), a large screech owl (Megascops guildayi (Brodkorb & Mourer-Chauviré 1984)), and the large goose, Branta dickeyi Miller 1924. It can be argued that none of these represent the extinction of a phyletic lineage during the Irvingtonian. Based on the broad habitat preferences of modern counterparts of the birds in the assemblage, we can expect that Irvingtonian habitats near the site included mixed forest with mast-producing hardwoods and both early and later successional stages represented. There must have been fluvial, wetland, or lacustrine habitat suitable for waterbirds nearby, and probably also open woodland or grassy savannah areas, suitable for vulture foraging, turkey nesting, and booming by Ruffed Grouse.